Investigation on Magnetic Properties of Soft/Hard Magnetic Bilayers at Different Temperatures: a Monte-Carlo Study - Deger, C.; Akoz, M. E.; Erkovan, M.; Yildiz, F. (POLISH ACAD SCIENCES INST PHYSICS, 2016)
Soft/hard magnetic bilayers are attractive systems for investigating their physical behavior due to scientific curiosity and the potential for technological applications. Thus, 10 nm thick hard magnetic layer placed on a 20 nm soft magnetic layer was modeled in this work. After the constructing of magnetic thin films, the bilayer structure was simulated based on micro-magnetic modeling. When constructing the Hamiltonian of the system, magnetocrystalline anisotropy term was also under debate with classical Zeeman and exchange terms. Energy minimization in the simulation was performed using Metropolis algorithm and Markov Chain Monte Carlo (MC-MC) method. As a result of modeling, hysteresis curves, remanent magnetization and coercive fields were obtained at different temperatures.
Keywords: FILMS; Physics